Problematika Pendidikan Islam di Indonesia Masa Kini dan Tantangannya di Masa yang Akan Datang : Penelitian - Wati, Heni Yuliana; Purwanto, Muhammad; Priyowahono, Bambang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to examine the problems and determine solutions to the problems of Islamic education. The results of the study and critical analysis concluded that the problems that occur in the world of Islamic education include moral decadence and the dichotomy of knowledge. The solution to the problems of Islamic education is to instill character values ​​and prevent the dichotomy of knowledge. The character values ​​are religious character values, religious attitudes and behaviors are attitudes and behaviors that are close to spiritual matters. Honesty is an attitude or behavior that is in accordance with words, thoughts, and actions, not lying, not cheating, and saying and acting honestly according to truth and facts. Tolerance forms students who have a sense of tolerance towards others. Hard work students need to be taught about the importance of hard work. Creativity is an ability to create something new, to provide new ideas that are applied in problem solving. Independence is a learning process for students should be directed to become independent students. Independence A learning process for students should be directed to become independent students.